The Effect of the Different Transgenic BT Cotton Technology on the Fiber Quality - Lubna Bashir Rajput; Jinjie Cui; Shuai Zhang; Junyu Luo; Chunvi Wang; Limin Lv (Journal of Basic & Applied Sciences, 2017)
Transgenic crops that contain Cry genes from B. thuringiensis (Bt) were commercialized in many countries and widely adopted by farmers over the last 17 years. The cultivation of transgenic crops expressing B. thuringiensis (Bt) toxins to control insect pests provides both economical and environmental benefits from reductions in chemical insecticide use, effective control of pests and minimal impact on non-target organisms. The objective of this research was to know the effect of different transgenic Bt cotton on the fiber quality of different Bt cotton varieties. Three transgenic Bt cotton varieties CCR141, CCRI79 and Bollgard II were planted in the field of Institute of Cotton Research Chinese Academy of Agricultural Sciences during 2012 and 2013. Randomly 50 bolls lint sample were collected from top, middle and bottom of the cotton plants. The fiber obtained from the boll samples was used to measure the cotton fiber staple length (mm), staple elongation (%), staple micronaire value, staple strength (cN/tex) and staple uniformity (%) by using HVI equipment at Supervision, Inspection and Testing Center of cotton Quality, China. The result shows that lint quality characters of transgenic cotton varieties were not significantly affected compared with conventional non Bt variety during 2012 and 2013 but fiber strength is significantly affected during 2013. In conclusion there was no effect of transgenic Bt cotton on the fiber quality of cotton during 2012 and 2013.